Impact of curricular internships in accounting on university students: an empirical study in Spain - Cristina Pérez-Espés; Mercedes Cervera Oliver; Francisca Cea D’Ancona (Revista de Contabilidad: Spanish Accounting Review, 2023)
Various organizations, commissions and committees highlight the importance of teaching future accounting professionals through the combination of theoretical training and professional practice. The university must guarantee an accounting profession through graduates who can respond to the needs and global changes of the society. Curricular internships, conducive to experiential learning, allow the student to integrate classroom learning with professional practice, as well as to translate abstract theoretical concepts into reality. An increasing number of universities include the subject of internships within their curricula. All of this makes it interesting to analyse the impact these internships have on university students. This article presents, through factor analysis and the technique of structural equations, a model that comprehensively evaluates the impact of curricular internships in the accounting field on students. The information necessary to estimate the model was obtained through a questionnaire presented to students at the end of their internship period. The survey was completed by 279 students belonging to the Degrees in Business Administration and Management and in Economics at the Autonomous University of Madrid.